Dyslexia: To be a Hand to Fly in the World of Word - John , Donit; Chandekar , Pratibha Arun (Dyslexia: To be a Hand to Fly in the World of Word, 2023)
Introduction: Dyslexia is the majority of a widespread learning disability in children. It's additionally referred to as a receptive language-based incapacity includes symptoms like an issue in mixing sounds into creating words, issue in tally syllables in words, the issue with naming syllables in words, an issue with naming words, poor writing system, and a habit of omitting and adding words or letters, whereas, writing and reading at the later ages. A dyslexic individual additionally has issues in memorizing, reading aloud, summarizing a story, and learning a far-off language. Most people are a unit of the opinion that each dyslexic reader moves letters around once they area unit reading. The role of Associate in nursing perceptive teacher in operating with a baby with a learning disorder is important, and their perception plays a vital role in learning for a baby United Nations agency has learning disordered. Lecturers’ area unit within the frontline and at the forefront of education that may facilitate a dyslexic kid attain. Comprehend a dyslexic beginner in a very cluster of scholars involve begin firm modify in a plan to create straightforward the educational method and create the learner feel safe and comfy. Our lecturers ought to create them responsive to the very fact that learning disorder could be a serious learning issue that unremarkable exists, however, is with success addressed and diminished. It is vital for future lecturers to own smart information and a positive perspective towards learning disorder, this might solve the matter of complications and alternative issues associated with dyslexic kids facing within the schoolroom and society. The structured teaching programme also will be provided in evidence-based observation with smart psychological support among dyslexic kids. Problem Statement: To evaluate the effectiveness of Structured Teaching Programme on Knowledge and Attitude regarding Dyslexia among Primary School Teachers in Aurangabad City. Objectives: To assess the existing knowledge score regarding dyslexia among primary school teachers. To assess the existing attitude score regarding dyslexia among primary school teachers. To correlate the knowledge and attitude among primary school teachers before the administration of structured teaching programme regarding dyslexia. To evaluate the effectiveness of structured teaching programme on knowledge and attitude regarding dyslexia among primary school teachers. To find-out the association between post-test knowledge score with their selected demographic variables. To find-out the association between post-test attitude score with their selected demographic variables. Hypothesis: H01-There is no significant difference between mean pre-test and post-test knowledge score of primary school teachers. H1- There is a significant difference between mean pre-test and post-test knowledge score of primary school teachers. H02- There is no significant difference between mean pre-test and post-test attitude score of primary school teachers. H2- There is a significant difference between mean pre-test and post-test attitude score of primary school teachers. H03- There is no significant correlation between knowledge and attitude of primary school teachers before the administration of a structured teaching programme. H3- There is a significant correlation between knowledge and attitude of primary school teachers before the administration of a structured teaching programme. H04- There is no significant association between post-test knowledge score with their selected demographic variables of primary school teachers. H4- There is a significant association between post-test knowledge score with their selected demographic variables. H05- There is no significant association between post-test attitude score with their selected demographic variables. H5- There is a significant association between post-test attitude score with their selected demographic variables. Results: The data gathered was analyzed and interpreted according to the objectives. Descriptive statistics were used. Mean percentage and standard deviation with the graphical representation of data were done. Inferential statistics were used at 0.05 levels of significance. Socio-Demographic Data: In concern with age, 60(24%) of the teachers had age 26-30 years, 110(44%) of them had age 31-35 years and 80(32%) of them had age above 36 years. There were no teachers from the age group of 20-25. In regards to gender, 120(48%) of them were males and130 (52%) of them were females. In concern with Professional qualification, 60(24%) of them were TTC, 100(40%) of them had B.Ed. And 90(36%) of them had M.Ed. There were no teachers have an additional degree. In regard with years of experience, 20(8%) of them had up to five years of experience, 60(24%) of them had 6 to 10 years of experience, 100(40%) of them had 11 to 15 years of experience and 70(28%) of them had above 15 years of experience. In concern with teaching time with students per day 30(12%) of them were teaching for up to 2 hours per day, 80(32%) of them were teaching for up to 4 hours and 140(56%) of them were teaching for up to 6 hours per day. There were no teachers have above 6 hours of teaching time with students. In concern with the number of students in the class, the majority of 130(52%) of them had 21-25 students in the class. 120(48%) of them had 26-30 students in class and none of them had below 20 and above 31 students in the class. In consider with nature of employment, 175(70%) of them were temporary and 75 (30%) of them were permanent. In regard to with previous experience with a dyslexic child, 170(68%) of them had no previous experience with dyslexic child 80(32%) of them had previous experience with dyslexic child. In considering with teachers undergone any short term training on a dyslexia, 170(68%) of them had never undergone any short term training on dyslexia and 80(32%) of them had attended in short term training and whereas 58(72.5%) participated in short term training, 22(27.5%) attended seminar, and none of them had take part in any workshop and conference on dyslexia. In regard with any committee regularly discussing about dyslexia, there were 130 (52%) teachers in the schools where have no committee regularly discussing about dyslexia and 120(48%) teachers in the schools where committee regularly discussing about dyslexia, and whereas 77(64%) had special educators and 43(36%) had mobile trainers to regularly discussing about dyslexia. Objective I: To assess the existing knowledge regarding dyslexia in Primary School Teachers. In the pre-test, the majority of 150(60%) of the primary school teachers had poor knowledge (score 0-10), 70(28%) of them had average knowledge (score 11-20) and 30(12%) of them had good knowledge (score 21-30) regarding dyslexia. Objective II: To assess the existing Attitude regarding dyslexia in Primary School Teachers In consider with pre-test, 220(88%) of the primary school teachers had a negative attitude (score 20-50) and 30(12%) of them had a positive attitude (Score 51-80) towards dyslexia. Objective III: To correlate the knowledge and attitude of primary school teachers before the administration of the Structured Teaching Programme Pearson’s correlation coefficient was used to assess the correlation between knowledge and attitude of primary school teachers regarding dyslexia. Pearson’s correlation coefficient was 0.14 which is positive. It indicates that there is a positive correlation between knowledge and attitude of primary teachers. The strength of this positive correlation was tested using the t-test for the significance of the correlation coefficient. The t-value for this test is 2.22 with 248 degrees of freedom. The corresponding p-value was small (less than 0.05). It is evident that there is a significant positive correlation between knowledge and attitude of primary teachers regarding dyslexia. More the knowledge better is the attitude of primary teachers towards dyslexia. Objective IV: To evaluate the Effectiveness of Structured Teaching Programme on Knowledge and attitude regarding Dyslexia In concern with knowledge pre-test, 150(60%) of the primary school teachers had poor knowledge (score 0-10), 70(28%) of them had average knowledge (score 11-20) and 30(12%) of them had good knowledge (score 21-30) regarding dyslexia, whereas. in the post-test, 30(12%) of the primary school teachers had poor knowledge (score 0-10), 80(32%) of them had average knowledge (score 11-20) and 140(56%) of them had good knowledge (score 21-30) regarding dyslexia. This indicates that the knowledge among primary school teachers regarding dyslexia improved remarkably after the structured teaching programme. A paired t-test was used to calculate the effect of STP on awareness of elementary school instructors regarding dyslexia. The average knowledge score in the pre-test was 11.1 whereas in the post-test score was 20.7. The t-value for this test was 21.8 with 249 degrees of freedom. It is evident that structured teaching is significantly effective in improving the knowledge regarding dyslexia among the primary school teachers. In regard to attitude the pre-test, 220(88%) of the primary school teachers had a negative attitude (score 20-50) and 30(12%) of them had a positive attitude (Score 51-80) towards dyslexia. In the post-test, 110(44%) of the primary school teachers had a negative attitude (score 20-50) and 140(56%) of them had a positive attitude (Score 51-80) towards dyslexia. This indicates that the attitude of the primary school teachers towards dyslexia improved remarkably after a structured teaching program. The paired t-test was used to evaluate the outcome of STP on awareness of graded school tutors regarding dyslexia. The average knowledge score in the pre-test was 44.5 which increased to 52.1 in the post-test. The t-value for this test was 15.5 with 249 degrees of freedom. It is evident that structured teaching is significantly effective in improving the attitude towards dyslexia among primary school teachers. Objective V: To find-out the association between Post-test knowledge score with their selected demographic variables. Among 10 demographic variables, 9 demographic variables were found to be significant (at 0.05 levels). According to calculated X2 value of age(X2 = 52.6),professional qualification(X2 =43.2), years of experience(X2 =111.1), teaching time with students per day(X2 =35.5), number of students in the class(X2 =10.8), nature of employment(X2 =15.4), previous experience with dyslexic child(X2 =23.5), any additional training on dyslexia(X2 =23.5), and do you have any committee regularly discussing about dyslexia(X2 =10.8)were found to have significant association with the knowledge regarding dyslexia among primary school teacher except gender(X2 =5.8). Objective VI: To find-out the association between Post-test attitude score with selected demographic variables. Among 10 demographic variables, 4 demographic variables were found to be having significant association (at 0.05 levels). According to calculated X2 value of gender (X2 =32.3), professional qualification (X2 =47.5), years of experience (X2 =28.9), and teaching time with students per day (X2 =11.3) were fvattitude of primary school teachers towards dyslexia. Whereas age in years (X2 =2.3),number of students in the class (X2 =0.3), nature of employment (X2 =0.2), previous experience with dyslexic child (X2 =1.6), have you undergone any additional training on dyslexia (X2 =1.6)and do you have any committee regularly discussing dyslexia (X2 =0.3) had no significant association between post-test attitude score with selected demographic variables. Conclusion: The findings revealed that Structured Teaching Programme was highly effective in increasing knowledge and having positive attitude regarding Dyslexia among Primary School teachers in Aurangabad City.